(untitled) (Damu Journal of Sport Sciences, 2024)
Research and investigation are ongoing through studies and research to find educational alternatives according to the intervention in the educational environment in a way that suits volleyball skills for the purpose of reaching effective teaching and evaluating the educational curriculum for volleyball in the curricula of colleges of physical education and sports sciences. The research aims to:- 1- Identify the effect of the total method and through intensive and distributed exercise on learning some volleyball skills. 2- Identify the best intervention in the total method with the intensive or distributed exercise method. The researcher used the experimental method of equal random groups to reach a solution to the research problem and achieve its objectives. The research sample included (20) students from the second phase / College of Physical Education and Sports Sciences / University of Diyala with a percentage of (20.20%) and the sample was divided into . The students were taught the skills of sending facing from above and preparing in volleyball for an educational period that included (8) educational units and for each week two educational units for a period of 4 weeks and a time of (90) minutes for each educational unit. The technical performance of the students was evaluated by the evaluators and by displaying it on (CD). Through statistical processing of the results, the researcher concluded the following: The emergence of a positive effect of groups in learning and retaining the skills of sending facing from above and receiving The emergence of the best interference in the group of the total method - intensive in the skill of sending facing from above